1998
DOI: 10.1002/(sici)1520-6327(1998)38:2<74::aid-arch3>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Fitness and feeding are affected in the two-spotted stinkbug,Perillus bioculatus, by the cysteine proteinase inhibitor, oryzacystatin I

Abstract: Plant resistance to insect pests based on recombinant proteinase inhibitors (Pis) could interfere with natural enemies of target pests, as their own proteolytic systems may also be sensitive to large spectrum PIs. Oryzacystatin I (OCI) is a potential insect pest resistance factor currently engineered into a variety of crop plants, including potato Solanum tuberosum. Potential for OCI interfering with female reproduction in Perillus bioculatus, a stinkbug predator of Colorado potato beetle, Leptinotarsa decemli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…This may be of particular importance when the expressed PI is targeted at a pest insect that is fed on by an insect predator that also utilises the same mechanistic class of digestive proteinases. The potential for PIs to have negative preymediated effects at the third trophic level has been the subject of several recent studies and some adverse effects of PIs on predators and parasitoids have been recorded (Ashouri et al, 1998;Bell et al, 2001). However, other studies have found few, if any, negative effects (PicardNizou et al, 1997;Bouchard et al, 2003a,b;Ferry et al, 2003).…”
Section: Introductionsupporting
confidence: 88%
“…This may be of particular importance when the expressed PI is targeted at a pest insect that is fed on by an insect predator that also utilises the same mechanistic class of digestive proteinases. The potential for PIs to have negative preymediated effects at the third trophic level has been the subject of several recent studies and some adverse effects of PIs on predators and parasitoids have been recorded (Ashouri et al, 1998;Bell et al, 2001). However, other studies have found few, if any, negative effects (PicardNizou et al, 1997;Bouchard et al, 2003a,b;Ferry et al, 2003).…”
Section: Introductionsupporting
confidence: 88%
“…Possibly JA-mediated defenses have an effect on egg development, since negative effects on the growth and development of Manduca sexta larvae have been found on tobacco after pretreatment with MeJA (Van Dam et al, 2000). Alternatively, JAmediated defenses may affect egg quality, since it was found that hatching of Perillus biocalatus (two-spotted stinkbug) eggs decreased as the level of Cys proteinase inhibitors increased (Ashouri et al, 1998). These results suggest that plant defenses can have an impact not only on juvenile development but also on egg viability.…”
Section: Spider Mites Perform Equally Well On Def-1 and Wild Typementioning
confidence: 99%
“…Complementary zymographic assays were carried out to measure the inhibitory potency of SlCYS8 variants against protease I, a major digestive Cys protease of the stinkbug predator Perillus bioculatus sensitive to plant cystatins (Ashouri et al, 1998;Overney et al, 1998;Fig. 4).…”
Section: Inhibitory Potency Against Stinkbug Predator Cys Proteasesmentioning
confidence: 99%